226k views
5 votes
4(5x - 2) = 2 (9x + 3) what is the answer?

2 Answers

5 votes

Heya!!

Here's your answer:-

4(5x-2)=2(9x+3)

2(5x-2)=9x+3 (dividing 2 on both sides)

10x-4=9x+3 (opening the brackets)

10x-9x=3+4 (Rearranging the like and unlike terms)

x=7

Hope it helps!!

User Cbinder
by
5.4k points
4 votes

Answer:

x = 7

Explanation:

Isolate the variable (x). Note the equal sign, what you do to one side, you do to the other. Remember to follow PEMDAS.

First, distribute 4 to all terms within the parenthesis it's connected to (5x & 2), as well as 2 to all terms within the parenthesis it's connected to (9x & 3).

4(5x - 2) = 4(5x) - 4(2) = 20x - 8

2(9x + 3) = 2(9x) + 2(3) = 18x + 6

20x - 8 = 18x + 6

Isolate the variable (x). Note the equal sign, what you do to one side, you do to the other. Add 8 & subtract 18x from both sides

20x (-18x) - 8 (+8) = 18x (-18x) + 6 (+8)

20x - 18x = 6 + 8

2x = 14

Isolate the variable (x). Divide 2 from both sides.

(2x)/2 = (14)/2

x = 14/2

x = 7

7 is your answer for x.

~

User LuizMello
by
5.8k points